(untitled) (Al-Academy, 2017)
This thesis study (pen weight and diversity of Arabic calligraphy), including the Arabic script went through multiple bodies, it came through the natural evolution of societies, and helped in the renovation and development of calligraphy after they gained a clear identity as a result of development that has occurred in the materials and writing instruments, especially industry pen that led to the diversity of Arabic calligraphy, and through the exploratory research and modeling study, which was obtained that the researcher could pose a problem discussed in the first chapter of his study follows by asking: is the pen is the weight of the role in the diversity of Arabic calligraphy? It embodied the importance of research through knowledge of measuring pen weight it’s written by various Arab lines and the method of its use, and this study may offer the benefit of researchers and scholars in the field of Arabic calligraphy, while the research was designed to detect the weight of pens and their role in the diversity of Arabic calligraphy for the duration of the era released Islam to the year (1410 -1991), while the second chapter included (two sections) the first topic dealt with the process of transformation of blogging to the line, and came second section of the pen weight (measurement) and its role in the naming of the Arab lines, followed by the theoretical framework indicators, but Chapter III has included research procedures, where the descriptive and analytical approach adopted, and it was the research community has reached (40) panel chose the researcher (4) intentional samples were analyzed according to the search of form for analysis tool which included three pillars oversaw the validity of a group of specialists in this field. The fourth chapter included the analysis of samples and display the results, including: 1. The weight of the pen (view age) has had a clear impact on the morphological characters show the structure of the board proportionate and consistent, as well as the regularity and proficiency of the type of line compared schedule. 2. The process of activating the diversity of Pen Weight eligible to meet many of the goals that will achieve the functional and the aesthetic and expressive calligraphy dimensions. 3. Helps the contrast between the letters and the list Almstgayh formal and diversity that it shows, in the art of calligraphy access to advanced stages objective aesthetic associated with a fixed rate of weight pens. 4. Finding a suitable weight to view the age of the line in the show pen letters of formal structure, as well as Ansiabatha and agility Abdanha, Tsad to ensure effective achievement linear beautiful, tajweed.